Potensi Antikanker Pada Ekstrak Etanol Makroalga Caulerpa racemosa Menggunakan Metode Brine Shrimp Lethality Test (BSLT) - Devi Ardiyati Khasana; Endang Linirin Widiastuti; Nuning Nurcahyani; Agus Setyawan; Ni Luh Gede Ratna Juliasih (Universitas Bangka Belitung, 2025)
Caulerpa racemosa is one of the green macroalgae that is widely distributed in the coastal areas of Lampung Province and needs to be explored as a phytopharmaceutical ingredient because it is thought to have bioactive compounds. In this study, we also used taurine, which is known to prevent cell and tissue damage due to oxidative processes, to explore its potential as an anticancer. The initial stage of this research is phytochemical screening of 96% ethanol extract of Caulerpa racemosa and contains phenolic compounds . alkaloids, saponins, flavonoids, tannins, steroids and terpenoids. The toxicity test of Caulerpa racemosa ethanol extract and taurine used the BSLT method (Brine Shrimp Lethality Test). In this study, 7 concentrations were used, namely 0 ppm (control); 62.5; 125; 250; 500; 1000; and 2000 for both Caulerpa racemosa and taurine ethanol extracts with 5 repetitions. Meanwhile, the toxicity test results showed that the LC50 value of Caulerpa racemosa ethanol extract was 194.14 ppm and 170.69 ppm for taurine, this values are between 100 ppm - 1000 ppm of Caulerpa racemosa ethanol and taurine indicate that both material have potential anticancer activity with low toxicity.